Soil characteristics and ecological thresholds of Suaeda salsa wetlands. Issue 1 (31st December 2022) - Qian, Fengkui; Zhou, Yang; Li, Wanning; Wang, Xiangguo; Sun, Zhentao; Liu, Guize; Wei, Haifeng
ABSTRACT: SSuaeda salsa is an annual euhalophyte in estuarine wetlands. Soil properties of wetlands have an important influence on S. salsa growth. Therefore, the soil ecological thresholds is valuable for the restoration of degraded S. salsa wetlands. The objectives of this present study were to analyze the soil physicochemical properties and evaluate the soil ecological thresholds in the typical degraded areas for S. salsa growth. Soil text components became coarser with increased sand contents and less clay contents, as the higher degree of wetland degradation. Meanwhile, the salt contents in different soil depths gradually increased with the increased degree of degradation of wetlands. Evident changes in soil water content, organic matter content, and cations concentrations were not observed, while the concentrations of these factors were higher in the soil layer of 0–10 cm than those in the 20–30 cm. The soil pH in the 0–10 cm soil layer was lower than that in the 20–30 cm. The content of the three available nutrients did not change evidently with the increasing degree of degradation. The optimum thresholds of soil salinity and water content were 7.073–16.613 g/kg and 31.8–63.2%, respectively.